Male Breast Cancer in Dr. Hasan Sadikin General Hospital: A Serial Case - Rantapina Kurnia Sari; Maman Abdurrahman; Monty Priosodewo Soemitro; Kiki Akhmad Rizki; Raden Yohana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Male breast cancer is a rare case. It accounts for 1% of all breast cancer cases. Both female and male breast cancers were influenced by the same risk factors. Male breast cancer patients are typically associated with advanced stages, higher grades, higher prevalence of hormone receptor-positive, and a worse prognosis. Many factors can explain the late diagnosis in men: absence of screening programs, lack of awareness about the condition by the male population, embarrassment due to a stigmatization of the disease, and misjudgment by primary care physicians. The aim of study is to improve the knowledge about the biology tumor and characteristics, risk factor, and management of male breast cancer. Case presentation: Two patients who were studied were a man with 50 years old, without malignancy on their family and testicles disease. First patients was diagnosed with mucinous adenocarsinoma grade II on right breast luminal A subtype T4bN0M0 and second patient was diagnosed with Ductal carcinoma in situ on right breast luminal B Her2 negative subtype TisN0M0 as preoperative diagnosis and Invasive solid papillary carcinoma grade III on right breast T2N0M0 as post operative diagnosis. Both of them were operated with modified radical mastectomy. First patient was given neoadjuvant chemotherapy, adjuvant chemotherapy and tamoxifen as endocrine therapy. Second patient was given adjuvant chemotherapy and tamoxifen as endocrine therapy. Conclusion: Both of patients on serial cases are male breast cancer with hormone receptor positive and they were given endocrine therapy. The majority characteristic of male breast cancer was hormone receptor-positive. Management of male breast cancer is similar overall to management of female breast cancer in modality surgery, chemotherapy, endocrine therapy, and radiotherapy.